Devolution and localism in England - Smith, David M. (David Michael) 1945-; Wistrich, Enid (Routledge is an imprint of the Taylor & Francis Group, an informa business, 2014)
Combining historical and policy study with empirical research from a qualitative study of regional elites this book offers an original and timely insight into the progress of devolution of governance in England